MARRIAGE IS SCARY DI MEDIA SOSIAL: TANGGAPAN KRITIS MELALUI PERSPEKTIF HADIS NABI - Aldi Wikaldi; Rasyid Alhafizh (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2025)
The decline in marriage rates in Indonesia recorded in 2024 marked the lowest figure since 1997/1998, indicating a significant social shift in the meaning attributed to the institution of marriage. This phenomenon is further reinforced by the social media trend entitled “Marriage is scary”, which has shaped negative perceptions of marriage, particularly among Generation Z. The circulating narratives portray marriage as an emotional and financial burden, as well as a space vulnerable to conflict and gender inequality. This study aims to construct a social understanding of marriage as shaped by social media narratives through the perspective of the Prophetic Hadiths of Muhammad. Employing a qualitative approach and comparative analysis, this research uses the theory of social constructivism and social exchange theory to understand how these perceptions are formed and disseminated. The findings show that the Hadiths of the Prophet offer educational, empathetic, and solution-oriented narratives regarding marriage. Values such as communication, simplicity, responsibility, and mutual respect between partners are emphasized as foundational elements in building a healthy household. Therefore, Hadiths can function as a counter-narrative capable of balancing the negative perceptions that are growing in digital spaces. Integrating Hadith values into communicative and contextual forms of digital preaching (dakwah) represents a strategic step in rebuilding a positive image of marriage.